2018
DOI: 10.1177/1077546318813401
|View full text |Cite
|
Sign up to set email alerts
|

Cusp bifurcation of slightly curved tensioned pipe conveying hot pressurized fluid

Abstract: In the course of operation of pipes conveying high temperature-high pressure fluid, unexpected behaviors leading to catastrophic failures have been observed. These have been attributed to uncertainties arising from issues not adequately addressed in the design. Sources of such uncertainties include geometric imperfection of the pipe and temperature variation. The perfectly straight pipe is assumed in most designs, but it is an idealization that does not exist in practice. In a bid to reduce the number of uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…This can be explained as Here, as temperature increases, a significant reduction in fundamental natural frequency and critical velocity is observed. Thus, the temperature variations have a softening effect on the pipe stiffness, which is consistent with the work of Ashley et al [32] where the natural frequency was found to be inversely proportional to the temperature and with the work of Orolu et al [33] where the critical velocity reduces with the increase of temperature. Also, it is noted that the temperature effect on the fundamental natural frequency and the critical velocity of the pipe conveying fluid is considerably growing at higher aspect ratio.…”
Section: Print Output Endsupporting
confidence: 89%
“…This can be explained as Here, as temperature increases, a significant reduction in fundamental natural frequency and critical velocity is observed. Thus, the temperature variations have a softening effect on the pipe stiffness, which is consistent with the work of Ashley et al [32] where the natural frequency was found to be inversely proportional to the temperature and with the work of Orolu et al [33] where the critical velocity reduces with the increase of temperature. Also, it is noted that the temperature effect on the fundamental natural frequency and the critical velocity of the pipe conveying fluid is considerably growing at higher aspect ratio.…”
Section: Print Output Endsupporting
confidence: 89%
“…Presently, the researches on the static performance of the pipes show that when the flow velocity exceeds the critical flow velocity, the fluid-conveying pipes appear static deformation (Orolu et al, 2019). Typically, the critical velocity is affected by the physical properties of the internal fluid (Giacobbi et al, 2020) and also depends on the pipes, such as boundary conditions (Ni et al, 2017), initial geometric imperfection (Wang et al, 2012), and viscoelastic foundation etc.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of pipe are also common in engineering. As a consequence, a few theoretical models, which could deal with the pipes with arbitrary shapes, were proposed [28][29][30][31][32][33]. For instance, based on the Hamilton's extended principle, a nonlinear theoretical model was proposed by Sinir [28] to investigate the nonlinear dynamics of a slightly curved fluid-conveying pipe with both ends supported.…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that the model developed in the present work has four advantages compared with those models mentioned in the Ref. [31][32][33][34][35][36][37][38][39][40]: (i) it can determine the extremely large-amplitude vibrations of the soft straight-curved combination pipes conveying fluid; (ii) it can be applied to the straight-curved combination pipes with arbitrary initially shapes, such as L-, Z-, U-, J-shaped pipes, etc. ; (iii) it can be applied to any boundary conditions, such as pinned-pinned, clamped-free, pinned-pinned-free and so on; (iv) it can handle not only the self-excited vibrations but also the forced oscillations.…”
Section: Introductionmentioning
confidence: 99%